2022
DOI: 10.1109/tbme.2021.3135313
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing the Role of Respiration in Cardiovascular and Cerebrovascular Variability Interactions

Abstract: Respiration disturbs cardiovascular and cerebrovascular controls but its role is not fully elucidated. Methods: Respiration can be classified as a confounder if its observation reduces the strength of the causal relationship from source to target. Respiration is a suppressor if the opposite situation holds. We prove that a confounding/suppression (C/S) test can be accomplished by evaluating the sign of net redundancy/synergy balance in the predictability framework based on multivariate autoregressive modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…The sympathetic nervous system seems to attenuate the CO 2induced increases in CBF (Jordan et al, 2000), which can be mediated by ventilation in the ICU. Though it has been noted that powerful actions of mechanical ventilation induces periodical modifications of the intrathoracic pressure, modulating venous return which has shown to alter cardiovascular and cerebrovascular interactions (Innes et al, 1993;Elstad et al, 2011;Porta et al, 2021). With literature assessing the relationship between PEEP and cerebral reactivity in pigs, demonstrating that static PEEP improved the assessment of impaired/intact cerebrovascular reactivity (Brady et al, 2012;Fraser et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nervous system seems to attenuate the CO 2induced increases in CBF (Jordan et al, 2000), which can be mediated by ventilation in the ICU. Though it has been noted that powerful actions of mechanical ventilation induces periodical modifications of the intrathoracic pressure, modulating venous return which has shown to alter cardiovascular and cerebrovascular interactions (Innes et al, 1993;Elstad et al, 2011;Porta et al, 2021). With literature assessing the relationship between PEEP and cerebral reactivity in pigs, demonstrating that static PEEP improved the assessment of impaired/intact cerebrovascular reactivity (Brady et al, 2012;Fraser et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We thus propose that the arterial baroreflex had no change in input and did not contribute to our results. Porta et al have found that respiration affects the cardiac baroreflex pathway by reduction of baroreflex sensitivity ( Porta et al, 2000 ; Porta et al, 2012 ; Porta et al, 2022) . Similarly, when baroreceptor stimuli occur during inspiration, the respiratory gate renders the vagal cardiac motoneuron unresponsive ( Eckberg, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this latter paper, the first application of Laguerre expansions to this problem was also reported. The use of multivariate autoregressive methods was recently presented in connection with the effects of respiration to this system ( Porta et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We note that the term “cerebral autoregulation” (CA or CAR) has been used by the peer community to describe the dynamic relation between ABP and CFV in the extensive literature on this matter [e.g. ( Aaslid et al, 1989 ; Paulson et al, 1990 ; Tiecks et al, 1995 ; Panerai, 1998 ; Zhang et al, 1998 ; Panerai et al, 1999 ; van Beek et al, 2008 ; Mitsis et al, 2009 ; Porta et al, 2022 )]. The term “cerebral flow autoregulation” (CFA) is used in this paper to draw the distinction with those previous studies with regard to the use of a second input (CO2) accounting for the contemporaneous effects on CFV of spontaneous changes in blood CO2 tension, as well as to make the object of autoregulation explicit.…”
Section: Introductionmentioning
confidence: 99%